2017
DOI: 10.1007/s10803-017-3069-5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Theory of Mind on Social Information Processing in Children With Autism Spectrum Disorders: A Mediation Analysis

Abstract: Individuals with autism spectrum disorders (ASD) show significant impairments in social skills and theory of mind (ToM). The aim of this study was to evaluate ToM and social information processing abilities in 52 children with ASD compared to 55 typically developing (TD) children. A mediation analysis evaluated whether social information processing abilities can be mediated by ToM competences. In our results, children with autism showed a deficit in social skills and ToM components. The innovative results of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
101
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 39 publications
5
101
0
1
Order By: Relevance
“…Happé, ) and there is evidence to support this (e.g. Mazza et al., ; for overview, see Brunsdon & Happé, ). Compensation becomes relevant when considering that some autistic individuals demonstrate fairly good social skills, despite clear sociocognitive atypicalities, as measured by sensitive ToM tasks (e.g.…”
Section: Introductionmentioning
confidence: 95%
“…Happé, ) and there is evidence to support this (e.g. Mazza et al., ; for overview, see Brunsdon & Happé, ). Compensation becomes relevant when considering that some autistic individuals demonstrate fairly good social skills, despite clear sociocognitive atypicalities, as measured by sensitive ToM tasks (e.g.…”
Section: Introductionmentioning
confidence: 95%
“…Less is known about the association of EF to emotion recognition abilities that are theoretically considered to be equally fundamental aspects of ToM and empathising in general (Golan et al, 2006). Indeed recent evidence has suggested that ToM should not be considered a single process as it includes two levels: cognitive and affective (Baron-Cohen et al 2015;Franco et al, 2014;Mazza et al, 2014Mazza et al, , 2017Shamay-Tsoory et al, 2009). Cognitive ToM refers to the ability to understand one's mental states (e.g.…”
Section: Ef and Tom In Asdmentioning
confidence: 99%
“…Cognitive ToM refers to the ability to understand one's mental states (e.g. what they're thinking), while affective ToM is the ability to infer one's emotions (Franco et al 2014;Mazza et al 2014Mazza et al , 2017. ToM tests such as the Reading the Mind in the Eyes (Baron-Cohen et al, 2001), despite tapping both mental state and emotion recognition abilities, are not as widely used in ASD.…”
Section: Ef and Tom In Asdmentioning
confidence: 99%
“…ASD manifests itself in early childhood and is characterized by a range of deficits in two domains, social communication, and social interaction, in addition to repetitive patterns of behavior (American Psychiatric Association, ). According to leading research in this field (Baron‐Cohen, Leslie, & Frith, ; Happé, Cook, & Bird, ; Mazza et al, ; Pino et al, ), the central core of autism is the impairment of social cognition (SC) abilities. SC is a complex cognitive process that refers to the capacity of people to store, process and apply information about other people and social contexts (Happé et al, ).…”
Section: Introductionmentioning
confidence: 99%